2016
DOI: 10.1161/atvbaha.115.306691
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-155 Promotes the Directional Migration of Resident Smooth Muscle Progenitor Cells by Regulating Monocyte Chemoattractant Protein 1 in Transplant Arteriosclerosis

Abstract: Objective— Smooth muscle–like cells are major cell components of transplant arteriosclerosis lesions. This study investigated the origin of the smooth muscle–like cells, the mechanisms responsible for their accumulation in the neointima, and the factors that drive these processes. Approach and Results— A murine aortic transplantation model was established by transplanting miR-155 −/− bone marrow cells into miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 32 publications
1
13
1
Order By: Relevance
“…However, miR-155-5p appears to play a conflicting role, either as pro-or anti-atherogenic, in the pathogenesis of atherosclerosis (44). Recently, advanced studies have clearly demonstrated that this miRNA is pro-atherogenic in a high fat-induced atherosclerosis model and a vascular injury model using miR-155 Ϫ/Ϫ mice (45,46), although they did not identify the target genes. Although miR-155-15 can target multiple mRNAs, we propose that it may play an important role in VSMC dysfunction by suppressing PKG1 expression in inflammatory conditions.…”
Section: Role Of Tnf-␣-induced Mir-155-5p In Vsmc Dysfunctionmentioning
confidence: 99%
“…However, miR-155-5p appears to play a conflicting role, either as pro-or anti-atherogenic, in the pathogenesis of atherosclerosis (44). Recently, advanced studies have clearly demonstrated that this miRNA is pro-atherogenic in a high fat-induced atherosclerosis model and a vascular injury model using miR-155 Ϫ/Ϫ mice (45,46), although they did not identify the target genes. Although miR-155-15 can target multiple mRNAs, we propose that it may play an important role in VSMC dysfunction by suppressing PKG1 expression in inflammatory conditions.…”
Section: Role Of Tnf-␣-induced Mir-155-5p In Vsmc Dysfunctionmentioning
confidence: 99%
“…13-16, 29-31, 68-70 An understanding of these phenotype transitions will most likely ultimately lead back to control of the SMC CArG box by myocardin and SRF together with the constellation of corepressors and coactivators that have been described to interact with this SMC differentiation platform. 32,71,72 Whether these phenotype transitions to macrophage-like, or osteoblast-like cell types are reversible in vivo , and what role resident SMC progenitor cells play in the homeostasis of the artery wall 73-77 are among the important questions going forward.…”
Section: Discussionmentioning
confidence: 99%
“…Smooth muscle-like cells (SMLCs) from the neointima of the outflow vein were isolated 3 weeks after AVF placement as previously described. 23 Briefly, the neointima was separated from the outflow vein under a light microscope and was digested in Dulbecco modified Eagle medium (DMEM) containing collagenase II (1 mg/mL; Worthington, Lakewood, NJ) at 37 C for 1 hour. The cells were then cultured in DMEM medium containing 10% fetal bovine serum and were used during passages three to seven.…”
Section: Author Contributionsmentioning
confidence: 99%